Riesgo de VIH/SIDA en la mujer: no es cuestión de estrato socioeconómico - María Fernanda Collazos (Colombia Médica, 2005)
Introduction: Women are now at the central place of the topic of HIV/AIDS spread at local and global level. In Colombia, theratio man:woman by 1987 year was 31:1, by 1995 year was 5:1 and by 2003 year was 2.6:1; these data confirm the feminization ofHIV/AIDS epidemic.Main objective: Identify protector and risk factors for HIV/AIDS in women from high socioeconomic status of Cali, Colombiawith the aim of recognizing high social class womens situation about vulnerability to HIV/AIDS.Methods: Descriptive study about risk and protection of HIV/AIDS of women from high socioeconomic status of Cali, Colombiawho participated answering a questionnaire. It was used the ball snow method for getting the sample of 95 women from Januaryto December of 2002 year. All the requierements asked from Institutional Review Board at University of Valle were met.Results: The findings show protective factors related with education, economic and family independence, high perception of empowerment and self-esteem. Few women reported domesticviolence and they did not use IV drugs; in contrast, they had riskfactors similar to those of low class women and perceivedinfidelity in their couple in spite of having a monogamous andheterosexual relationship. Although their self-perception aboutvulnerability to HIV/AIDS was high, condom use and power ofdecision in sexual relationships were low. Women had wrongbelieves about HIV/AIDS in spite of their high education.Conclussions: Women from high socioeconomic statuscompared to low class women had similar risk factor for HIV/AIDS, mainly those related to cultural aspects and gender role.It is recommended that promotion of the womens sexual healthaims to increase autonomy, self-efficacy in the relationshipswith their couples and the skills for negotiation of preventiveand protective practices. Risk factors related to social andcultural sphere should be part of the public debate and of theagenda of the health sector. The education in this aspect shouldtranscend the level of information to be located in the level oftransformation for empowerment and promotion of womenshealth.